Partial differential equations - DuChateau, Paul; DuChateau, Paul.; Zachmann, David W. (New York : McGraw Hill, 2011)
Fully compatible with your classroom text, Schaum's highlights all the important facts you need to know. Use Schaum's to shorten your study time-and get your best test scores! --Book Jacket
Includes index
"290 fully solved problems"--Cover
ntroduction -- Classification and characteristics -- Qualitative behavior of solutions to elliptic equations -- Qualitative behavior of solutions to evolution equations -- First-order equations -- Eigenfunction expansions and integral transforms : theory -- Eigenfunction expansions and integral transforms : applications -- Green's functions -- Different methods for parabolic equations -- Difference methods for hyperbolic equations -- Difference methods for elliptic equations -- Variational formulation of boundary value problems -- Variational approximation methods -- The finite element method : an introduction
Differential equations, Partial
Previously entitled: Schaum's outline of theory and problems of partial differential equations
Keywords: Differential equations, Partial -- Study guides; Problems and exercises; Differential equations, Partial -- Study guides; Differential equations, Partial -- Problems, exercises, etc; Mathematics -- Study guides